Os ilustradores de Lobato e as suas interpretações de Narizinho, de 1920 a 1970: uma comparação entre o texto e a construção gráfica da personagem - Lima, Joaes Cabral de (2024)
Based on the need to obtain new and greater discussions about the illustrators of Monteiro Lobato's works, in perspectives that not only broaden our knowledge of these artists, but that bring a renewal in the reading of the compositions and influences of the art of each one of them, as well as, of course, the history of Brazilian book illustration itself, so lacking in work that gives more visibility to its creators, the aim of this work is to analyze the evolution of the Lobatian character, Narizinho, in an attempt to expose and discuss the traces of Brazilianness that exist in its graphic representation and how close it is to what was idealized by its creator in the written text. And, in this way, to investigate the life and main works of the artists behind the illustrations of Lobato's children's works, highlighting how the advertising space and illustrated magazines were significant niches for illustrators who built a whole legacy of book graphic art in Brazil. To this end, from a cultural-historical perspective, the research we intend to develop goes beyond being merely descriptive. Therefore, as this is a bibliographical, comparative and discursive analysis, it is necessary to organize the course of the research in terms of the nature of the available sources, whether printed or electronic. We emphasize that over time, not only has the textual structure changed, but also the physical aspect of the character Narizinho has undergone a transformation, although not in relation to the text, but in relation to her body, after all, through the illustrations, we show the changes that occur with the character. It's about the girl giving way to a woman. As a theoretical contribution, we required support from Arroyo (1990), Camargo (1995), Koshiyama (2006), Lima (2019), among other illustration scholars.